Lithium-sulfur battery
By using sulfur-carbon composite materials in the positive electrode of lithium-sulfur battery and optimizing the weight ratio of electrolyte to sulfur, the problem of low capacity retention rate of lithium-sulfur batteries at high discharge speed is solved, and the effect of high energy density and high capacity retention rate is achieved.
Patent Information
- Application Number
- CN202380046596.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-05-23
- Filing Date
- 2023-12-18
- Publication Date
- 2025-03-28
AI Technical Summary
The efficiency of the gradual conversion reaction of existing lithium-sulfur batteries at high discharge speeds is low, resulting in a significant reduction in capacity retention rate in repeated charge and discharge cycles, and the charge and discharge efficiency is very low.
By using sulfur-carbon composite materials in the positive electrode of lithium-sulfur battery and optimizing the weight ratio of sulfur in the electrolyte to sulfur-carbon composite materials, the capacity retention rate and charge and discharge efficiency of lithium-sulfur batteries at high discharge speeds are improved.
At a discharge rate of 1.0C or above, such as 2.0C, lithium-sulfur batteries have high capacity retention and high energy density, which are specifically manifested as an energy density of more than 300 Wh/kg and a capacity retention rate of more than 85%.
Smart Images

Figure CN119731820A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a lithium-sulfur battery, and more particularly, to a lithium-sulfur battery achieving high capacity at a high discharge rate.
[0002] This application claims priority to Korean Patent Application No. 10-2023-0066600 filed in Korea on May 23, 2023, the disclosure of which is incorporated herein by reference. Background Art
[0003] As lithium secondary batteries are used in a wide range of applications including portable electronic devices as well as electric vehicles (EVs) and power storage systems (ESSs), there is an increasing demand for lithium secondary batteries with high capacity, high energy density, and long life.
[0004] Among lithium secondary batteries, lithium-sulfur batteries are battery systems that use a sulfur-based material containing a sulfur-sulfur bond as its positive electrode active material and use lithium metal, a carbon-based material in which insertion / extraction of lithium ions occurs, silicon or tin that forms an alloy with lithium, etc. as its negative electrode active material.
[0005] In lithium-sulfur batteries, sulfur, the main component of the positive electrode active material, has a low atomic weight, is abundant in nature, can be found all over the world, and is non-toxic and environmentally friendly.
[0006] In addition, when lithium metal is used in the negative electrode, the lithium-sulfur battery is composed of the conversion reaction of lithium ions and sulfur at the positive electrode (S8+16Li + +16e - →8Li2S) has a theoretical specific capacity of 1,675 mAh / g and a theoretical energy density of 2,600 Wh / kg. Compared with the theoretical energy density of other battery systems currently under research (Ni-MH battery: 450 Wh / kg, Li-FeS battery: 480Wh / kg, Li-MnO2 battery: 1,000 Wh / kg, Na-S battery: 800 Wh / kg, lithium-ion battery: 250 Wh / kg), the theoretical energy density of lithium-sulfur batteries is very high, so among the secondary batteries currently under development, lithium-sulfur batteries are attracting attention as lithium secondary batteries with high capacity, environmental protection and low cost.
[0007] The mechanism of lithium-sulfur batteries is as follows: During discharge, sulfur (S8) at the positive electrode accepts electrons and undergoes a multi-step reduction reaction to convert into lithium polysulfide (LiPS, Li2S x , x = 2 to 8) and is ultimately converted into lithium sulfide (Li2S), and in this case, the lithium-sulfur battery releases energy when converted into various materials.
[0008] Lithium-sulfur batteries are promising next-generation batteries for fields where energy density is important, such as aviation. To achieve the high output characteristics of lithium-sulfur batteries, efficient conversion of lithium polysulfide (LiPS) at high discharge rates (C rates) is required, especially from Li2S8 to Li2S2 and finally to lithium sulfide (Li2S). In particular, given the physical properties required for drones with a minimum usage time of about 30 minutes, they may require the ability to release sufficient energy during continuous discharge at a discharge rate of 2.0C.
[0009] However, it is reported that the lithium-sulfur batteries currently under development have low efficiency of step-wise conversion reactions at high discharge rates, resulting in a significant decrease in capacity retention during repeated charge and discharge cycles, and very low charge and discharge efficiency. As a result, the capacity of currently developed lithium-sulfur batteries is lower than the theoretical capacity when the discharge rate is increased by increasing the output.
[0010] Therefore, there is a need to develop lithium-sulfur batteries with sufficient capacity at high discharge rates. Summary of the invention
[0011] Technical issues
[0012] The present invention aims to solve the above-mentioned problems, and thus the present invention aims to provide a lithium-sulfur battery having a high capacity retention rate under high output conditions.
[0013] In particular, the present invention aims to provide a lithium-sulfur battery having a high capacity retention rate at a discharge rate (C-rate) of 1.0C or more, for example, 2.0C.
[0014] Technical Solution
[0015] In order to solve the above problems, according to one aspect of the present invention, a lithium-sulfur battery according to the following exemplary embodiment is provided.
[0016] A lithium-sulfur battery according to a first exemplary embodiment includes:
[0017] a positive electrode; a negative electrode; a separator between the positive electrode and the negative electrode; and an electrolyte,
[0018] wherein the positive electrode has a positive electrode active material comprising a sulfur-carbon composite material, and
[0019] The lithium-sulfur battery has a ratio R (1.0C / 0.5C) of more than 80%, and the ratio satisfies the following mathematical formula 1:
[0020] [Mathematical formula 1]
[0021] R(1.0C / 0.5C)=[A(DoD 100) 1.0C / A(DoD 100) 0.5C]×100 (%)
[0022] In mathematical formula 1,
[0023] A(DoD 100) 1.0C is the amount of lithium sulfide (Li2S) present at a depth of discharge (DoD) of 100 after discharge at 1.0C, and
[0024] A(DoD 100) 0.5C is the amount of lithium sulfide (Li2S) present at DoD 100 after discharge at 0.5C.
[0025] According to the second exemplary embodiment, in the first exemplary embodiment, R(1.0C / 0.5C) may be 85% or more.
[0026] According to the third exemplary embodiment, in the first or second exemplary embodiment, the DoD 100 may be in a state having a potential of 1.7 to 1.9 V.
[0027] According to the fourth exemplary embodiment, in any one of the first to third exemplary embodiments, the DoD 100 may be in a state having a potential of 1.8 V.
[0028] According to the fifth exemplary embodiment, in any one of the first to fourth exemplary embodiments, the amount of lithium sulfide (Li 2 S) may be the weight, volume or mole of lithium sulfide.
[0029] According to the sixth exemplary embodiment, in any one of the first to fifth exemplary embodiments, the ratio R (1.0C / 0.5C) can be measured by the ratio of the peak intensity of lithium sulfide (Li2S) in the X-ray diffraction spectrum of the lithium-sulfur battery, and the lithium sulfide (Li2S) can be in the range of 1.85 to 1.92 Å in the X-ray diffraction spectrum. -1 There is a characteristic peak in the scattering vector (q) region.
[0030] According to the seventh exemplary embodiment, in any one of the first to sixth exemplary embodiments, a weight ratio of the electrolyte to sulfur (S) in the sulfur-carbon composite material (E1 / S weight ratio) may be 2.7 g / g or more.
[0031] According to an eighth exemplary embodiment, in any one of the first to seventh exemplary embodiments, the electrolytic solution may include a nonaqueous solvent, a lithium salt, and an additive.
[0032] According to the ninth exemplary embodiment, in any one of the first to eighth exemplary embodiments, the energy density of the lithium-sulfur battery may be 300 Wh / kg or more.
[0033] According to the tenth exemplary embodiment, in any one of the first to ninth exemplary embodiments, the amount of sulfur (S) in the sulfur-carbon composite material may be 60 to 85 wt %.
[0034] According to the eleventh exemplary embodiment, in any one of the first to tenth exemplary embodiments, the weight of the sulfur-carbon composite material may be 90 wt % or more based on the total weight of the positive electrode.
[0035] According to the twelfth exemplary embodiment, in any one of the first to eleventh exemplary embodiments, the lithium-sulfur battery may be a coin-type battery, a pouch-type battery, or a cylindrical battery.
[0036] According to another aspect of the present invention, an evaluation method according to the following exemplary embodiment is provided.
[0037] An evaluation method according to a thirteenth exemplary embodiment is a method for evaluating output characteristics of a lithium-sulfur battery, the lithium-sulfur battery comprising: a positive electrode; a negative electrode; a separator between the positive electrode and the negative electrode; and an electrolyte, wherein the positive electrode has a positive electrode active material comprising a sulfur-carbon composite material, and the evaluation method comprises the following steps:
[0038] When the ratio R (1.0C / 0.5C) according to the following mathematical formula 1 is 80% or more, it is determined to be a high-power lithium-sulfur battery,
[0039] [Mathematical formula 1]
[0040] R(1.0C / 0.5C)=[A(DoD 100) 1.0C / A(DoD 100) 0.5C ]×100 (%)
[0041] In mathematical formula 1,
[0042] A(DoD 100) 1.0C is the amount of lithium sulfide (Li2S) present at DoD 100 after discharge at 1.0C, and
[0043] A(DoD 100) 0.5C is the amount of lithium sulfide (Li2S) present at DoD 100 after discharge at 0.5C.
[0044] According to the fourteenth exemplary embodiment, in the thirteenth exemplary embodiment, the high-output lithium-sulfur battery may be a battery that maintains an energy density of 300 Wh / kg or more under a discharge condition of 1.0 C rate or more at room temperature.
[0045] According to the fifteenth exemplary embodiment, in the thirteenth or fourteenth exemplary embodiment, the room temperature may be 23°C to 25°C.
[0046] According to a sixteenth exemplary embodiment, in any one of the thirteenth to fifteenth exemplary embodiments, A(DoD 100) x C (x = 0.5 or 1.0) can be determined by looking at the X-ray diffraction spectra obtained at DoD 100 after the Li-S battery was discharged at x C rate in the range of 1.85 to 1.92 Å. -1 The ratio R (1.0C / 0.5C) can be measured by calculating the ratio of the peak intensities obtained.
[0047] Beneficial Effects
[0048] The lithium-sulfur battery according to one aspect of the present invention has sufficient energy density and capacity at a high discharge rate.
[0049] Specifically, when the lithium-sulfur battery is discharged at a rate of 1.0C or higher, it can also maintain the same high energy density and capacity as when it is discharged at a rate of 0.5C.
[0050] In particular, the lithium-sulfur battery of the present invention may have a specific capacity of 1,000 mAh / g or more.
[0051] In particular, the lithium-sulfur battery of the present invention may have an energy density of 300 Wh / kg or more. BRIEF DESCRIPTION OF THE DRAWINGS
[0052] The accompanying drawings show exemplary embodiments of the present invention and, together with the foregoing description, are used to provide a further understanding of the technical aspects of the present invention, and therefore, the present invention should not be construed as being limited to the accompanying drawings. In the accompanying drawings, the shape, size, dimension or ratio of the elements may be exaggerated for clarity of description.
[0053] Figure 1 The discharge rate (C rate)-energy density graph of the lithium-sulfur batteries of Example 1, Example 2 and Comparative Example 1 is shown.
[0054] Figure 2 The specific capacity-voltage graph of the lithium-sulfur batteries of Example 1, Example 2 and Comparative Example 1 is shown.
[0055] Figure 3 The nominal voltages of the lithium-sulfur batteries of Example 1, Example 2 and Comparative Example 1 at a discharge rate of 0.5C and a discharge rate of 1.0C are shown.
[0056] Figure 4 is a graph showing the amount of Li2S generated when the lithium-sulfur batteries of Example 1, Example 2, and Comparative Example 1 were discharged at a 0.5C rate.
[0057] Figure 5 is a graph showing the amount of Li2S generated when the lithium-sulfur batteries of Example 1, Example 2, and Comparative Example 1 were discharged at a 1.0C rate. DETAILED DESCRIPTION
[0058] Hereinafter, the present invention will be described in more detail.
[0059] It should be understood that the terms or words used in the specification and the appended claims should not be interpreted as limited to the ordinary and dictionary meanings, but should be interpreted according to the meanings and concepts corresponding to the technical aspects of the present invention, based on the principle that the inventors appropriately define the terms for the best interpretation.
[0060] The terms used herein are only used to describe the purpose of specific embodiments and are not intended to limit the present invention. As used herein, unless the context clearly indicates otherwise, the singular form also includes the plural form. It should be understood that when used in the specification, the term "comprising" or "including" clearly defines the existence of the features, integers, steps, operations, elements, compositions or combinations thereof, but does not exclude the existence or addition of one or more other features, integers, steps, operations, elements, compositions or combinations thereof.
[0061] Furthermore, unless otherwise specified, when used in the present specification, the terms “comprise” or “include” specify the presence of stated elements, but do not preclude the presence or addition of one or more other elements.
[0062] In the present invention, A and / or B means A or B or both.
[0063] In the present invention, "C rate" refers to a current rate and is a value indicating a speed at which a battery is charged or discharged. In the present invention, "C rate" may be abbreviated as "C".
[0064] In the present invention, unless otherwise specified, the temperature is expressed in degrees Celsius, with the unit being °C.
[0065] The term "composite material" as used herein refers to a material having physically and chemically different phases and more effective functions formed by combining two or more materials.
[0066] As used herein, the term "(poly)sulfide" encompasses "(poly)sulfide ions (S x 2- , 1≤x≤8)” and “(poly)lithium sulfide (Li2S x or Li2S x - , 1≤x≤8)” concept.
[0067] As used herein, the term "polysulfide" encompasses "polysulfide ions (Sx 2- “,1 < x ≤ 8)” and “polysulfide lithium (Li2S x or Li2S x - “, 1 < x ≤ 8)”.
[0068] During discharge, when the starting material sulfur (S8) at the positive electrode is converted into polysulfide lithium (LiPS) and then into lithium sulfide (Li2S), the lithium-sulfur battery releases energy.
[0069] According to one aspect of the present invention, there is provided a lithium-sulfur battery that enables a stable conversion reaction at a high discharge rate.
[0070] A lithium-sulfur battery according to one aspect of the present invention includes: a positive electrode; a negative electrode; a separator between the positive electrode and the negative electrode; and an electrolyte, wherein the positive electrode has a positive electrode active material containing a sulfur-carbon composite material.
[0071] In this case, the amount of Li2S generated when the lithium-sulfur battery is discharged to a DoD (depth of discharge) of 100 at a rate of 1.0 C is more than 80% of the amount of Li2S generated when discharged to a DoD of 100 at a rate of 0.5 C.
[0072] In an exemplary embodiment of the present invention, the amount of Li2S generated when the lithium-sulfur battery is discharged to a DoD (depth of discharge) of 100 at a rate of 1.0 C can be more than 85% of the amount of Li2S generated when discharged to a DoD of 100 at a rate of 0.5 C.
[0073] In an exemplary embodiment of the present invention, the sulfur-carbon composite material may include at least one of sulfur and sulfur compounds. Herein, sulfur compounds are collectively referred to as sulfur (S)-containing materials.
[0074] When the sulfur-carbon composite material contains sulfur (S8), polysulfide lithium is generated by a reduction reaction at the positive electrode during discharge of the lithium-sulfur battery. When polysulfide lithium is dissolved in the electrolyte and leaks from the positive electrode into the electrolyte, during the charging process of the lithium-sulfur battery, a small amount of polysulfide lithium is oxidized at the positive electrode, resulting in a low capacity of the lithium-sulfur battery.
[0075] Sulfur compounds may include, for example, any sulfur-containing compound that can be formed by a reduction reaction of inorganic sulfur (S8) or an oxidation reaction of lithium sulfide (Li2S), more specifically lithium sulfide (Li2S), polysulfide lithium (Li2S x “, 1 < x ≤ 8), disulfide compounds, carbon-sulfur polymers ((C2S y ) n “, y = 2.5 to 50, 2 ≤ n) or two or more thereof.
[0076] When a lithium-sulfur battery contains inorganic sulfur (S8) as a positive electrode active material, during discharge of the lithium-sulfur battery, sulfur is reduced to polysulfide (Li2S x , 1 < x ≤ 8) at the positive electrode, and the polysulfide is further reduced to lithium sulfide (Li2S). However, when the lithium-sulfur battery is discharged at a high C rate, the amount of polysulfide (Li2S) generated during discharge may be reduced due to poor reduction reaction, resulting in a serious decrease in capacity.
[0077] When a conventional lithium-sulfur battery is discharged at a high C rate, the reduction reaction efficiency at the positive electrode is low, resulting in a decrease in battery capacity.
[0078] However, in the lithium-sulfur battery according to an aspect of the present invention, the amount of Li2S generated when discharged to DoD 100 at 1.0 C is 80% or more, specifically 85% or more, compared to the amount of Li2S generated when discharged to DoD 100 at 0.5 C, so that the capacity decrease at a high discharge rate is less than the capacity decrease at a low discharge rate.
[0079] In the present invention, DoD 100 refers to a fully discharged state, that is, based on the state of charge (SoC) of 100%, that is, the fully charged state, and DoD is 100%. The DoD 100 can also be expressed as SoC 0%.
[0080] In an exemplary embodiment of the present invention, DoD 100 can be, for example, a state having a potential of 1.7 to 1.9 V, specifically a state having a potential of 1.8 V, but the present invention is not limited thereto.
[0081] Specifically, a lithium-sulfur battery having a ratio R(1.0C / 0.5C) of 80% or more can have high output characteristics, and the ratio satisfies the following Mathematical Formula 1.
[0082] [Mathematical Formula 1]
[0083] R(1.0C / 0.5C)=[A(DoD 100) 1.0C / A(DoD 100) 0.5C ×100 (%)
[0084] In the above Mathematical Formula 1,
[0085] A(DoD 100) 1.0C is the amount of lithium sulfide (Li2S) present in the state of being discharged to DoD 100 at 1.0 C, and
[0086] A(DoD 100) 0.5C is the amount of lithium sulfide (Li2S) present in the state of being discharged to DoD 100 at 0.5 C.
[0087] According to the above mathematical formula 1, the ratio of the amount of lithium sulfide generated when the lithium-sulfur battery is fully discharged at a rate of 1.0C (i.e., DoD 100) to the amount of lithium sulfide generated when the lithium-sulfur battery is fully discharged at a rate of 0.5C can be obtained. The higher the ratio, the higher the S8→Li2S in the positive electrode active material under high output conditions. x (x=2 to 8) → the higher the conversion rate of Li2S (lithium sulfide).
[0088] In an exemplary embodiment of the present invention, the ratio R (1.0C / 0.5C) of lithium sulfide (Li2S) may be specifically 88% or more or 90% or more. For example, the ratio R (1.0C / 0.5C) of lithium sulfide (Li2S) may be 80% to 100%, 85% to 100%, 88% to 99%, 90% to 95%, 85% to 93%, 88% to 93%, 90% to 93%, or 91% to 93%.
[0089] In the present invention, the amount of lithium sulfide (Li2S) can be expressed by weight, volume or mole. To measure the ratio, A (DoD 100) is measured using the same standard. 1.0C and A(DoD 100) 0.5C In the case of, the "amount" is not particularly limited to weight, volume or molar number.
[0090] In an exemplary embodiment of the present invention, the amount of Li2S in a lithium-sulfur battery in a discharged state can be measured in a destructive manner, that is, by disassembling the battery to analyze the amount of Li2S in the battery, but it can be preferably measured in a non-destructive manner to prevent the loss of Li2S in the battery and shorten the analysis time.
[0091] For example, the amount of Li2S in a lithium-sulfur battery in a discharged state can be measured by nondestructive X-ray diffraction (XRD) analysis. Specifically, Li2S is present in the range of 1.85 to 1.92 Å in the spectrum obtained by X-ray diffraction analysis. -1 The scattering vector (q) region has a characteristic peak. Therefore, it can be seen that -1 The ratio of the amount of Li2S is measured by the ratio of the peak intensities (i.e., scattering intensities) in the XRD patterns of lithium-sulfur batteries discharged to DoD 100 at different discharge rates in the scattering vector (q) region.
[0092] Therefore, in an exemplary embodiment of the present invention, the ratio R (1.0C / 0.5C) can be measured by the ratio of the peak intensity of lithium sulfide (Li2S) in the X-ray diffraction spectrum of the lithium-sulfur battery, and lithium sulfide (Li2S) can be measured at 1.85 to 1.92 Å in the X-ray diffraction spectrum. -1There is a characteristic peak in the scattering vector (q) region.
[0093] In an exemplary embodiment of the present invention, A(DoD 100) x C (x = 0.5 or 1.0) can be obtained by X-ray diffraction spectra of lithium-sulfur batteries at DoD 100 after discharge at x C rate, with the range of 1.85 to 1.92 Å -1 That is, the ratio R(1.0C / 0.5C) can be measured by the following steps: obtaining an X-ray diffraction spectrum of a lithium-sulfur battery at DoD 100 after discharge at 0.5C rate; -1 Substitute the peak intensity value in the scattering vector (q) region into A(DoD 100) 0.5C Then, an X-ray diffraction spectrum of the lithium-sulfur battery at DoD 100 after discharge at 1.0C rate is obtained; the X-ray diffraction spectrum obtained is between 1.85 and 1.92 Å -1 Substitute the peak intensity value in the scattering vector (q) region into A(DoD 100) 1.0C and calculate the ratio of the obtained peak intensities.
[0094] In an exemplary embodiment of the present invention, an X-ray diffraction spectrum may be obtained by irradiating a lithium-sulfur battery with X-rays having a wavelength (λ) = 0.7 to 0.8 Å at room temperature.
[0095] In an exemplary embodiment of the present invention, an X-ray diffraction spectrum may be obtained by irradiating a lithium-sulfur battery with an X-ray having a wavelength (λ) = 0.709 Å at room temperature.
[0096] Specifically, XRD analysis can be performed by real-time X-ray diffraction (Operando XRD) analysis during battery operation. More specifically, the XRD pattern can be obtained by measuring 2theta (2θ) in the range of 4° to 17° in transmission mode using Mo Kα X-rays (λ=0.709 Å) of PANalyicalEmpyrean XRD at room temperature (23°C). In this case, a pattern can be obtained at intervals of 0.014° for a total of 1 minute.
[0097] After measuring the ratio of the amount of Li2S measured in each discharge state by the above method, a lithium-sulfur battery having a ratio of 80% or more, specifically 85% or more can be defined as a lithium-sulfur battery having high output characteristics.
[0098] The various components of lithium-sulfur batteries are described in detail below.
[0099] positive electrode
[0100] In an exemplary embodiment of the present invention, the positive electrode may include a positive electrode current collector and a positive electrode active material layer on one or both surfaces of the positive electrode current collector.
[0101] The positive electrode current collector is not limited to a specific type, and may include any positive electrode current collector that supports the positive electrode active material and has high conductivity without causing any chemical changes in the battery. For example, the positive electrode current collector may include: copper, stainless steel, aluminum, nickel, titanium, palladium, sintered carbon; copper or stainless steel treated with carbon, nickel or silver on the surface; aluminum-cadmium alloy, etc.
[0102] The positive electrode current collector may have fine concavoconvexities on the surface to increase the bonding strength with the positive electrode active material, and may be in various forms such as films, sheets, foils, screens, nets, porous bodies, foams, nonwoven fabrics, and the like.
[0103] The positive electrode active material layer contains a positive electrode active material, and may further contain a conductive material, a binder, an additive, and the like.
[0104] In an exemplary embodiment of the present invention, the positive electrode active material includes a sulfur-carbon composite material.
[0105] In an exemplary embodiment of the present invention, the sulfur-carbon composite material may include: a porous carbon material; and a sulfur compound loaded on at least one of the pores of the porous carbon material or the outer surface of the porous carbon material. Since sulfur itself as a positive electrode active material does not have conductivity, sulfur can be used in combination with a conductive material such as a carbon material, and the porous carbon material can be used as a carrier of sulfur. In addition, a sulfur compound is added as a positive electrode active material, and may include, for example, inorganic sulfur (S8), lithium sulfide (Li2S), lithium polysulfide (Li2S x , 1≤x≤8), disulfide compounds, carbon-sulfur polymers ((C2S y ) n , y=2.5 to 50, 2≤n) or two or more thereof. Preferably, the sulfur compound may be inorganic sulfur (S8).
[0106] In an exemplary embodiment of the present invention, a porous carbon material as a positive electrode active material is used as a carrier of a sulfur compound and is used to provide a skeleton for uniformly and stably fixing the sulfur compound and improving the conductivity of the positive electrode. The porous carbon material is not limited to a specific type and may include any type of porous carbon material.
[0107] Porous carbon materials can generally be manufactured by carbonizing various carbon precursors. The porous carbon material contains irregular pores therein. The average diameter of the pores may be in the range between 1 and 200 nm, and the porosity may be in the range between 10 and 90% by volume of the total volume of the porous carbon material. When the average diameter of the pores is less than the above range, the pore size is only at the molecular level, making it impossible to load sulfur. On the contrary, when the average diameter of the pores exceeds the above range, the porous carbon material is not suitable for use in the electrode manufacturing process because of its low mechanical strength.
[0108] In an exemplary embodiment of the present invention, the "average diameter of the pores" can be measured by any known method for measuring the pore size of a porous material without limitation. For example, the pore size can be measured by scanning electron microscopy (SEM), field emission electron microscopy, laser diffraction or BET (Brunauer-Emmett-Teller) method. For example, a commercially available laser diffraction particle size analyzer (e.g., Microtrac MT 3000) can be used to perform measurements using laser diffraction. In addition, the BELSORP series analyzer of BEL Japan can be used to measure by the BET method, but is not limited thereto.
[0109] In an exemplary embodiment of the present invention, "porosity" refers to the ratio of the volume occupied by pores to the total volume of the structure in %, and can be used interchangeably with the terms pore ratio, void ratio, etc. The present invention is not limited to a specific method for measuring porosity, and in an exemplary embodiment of the present invention, porosity can be measured by a BET method using nitrogen, a mercury (Hg) porosimeter method, or ASTM D2873.
[0110] The porous carbon material may be in the shape of a sphere, a rod, a point, a tube, or a block and is not limited to a specific shape, and may be any shape commonly used in lithium-sulfur batteries.
[0111] The porous carbon material may include any porous carbon material having a porous structure and a large specific surface area. For example, the porous carbon material may include at least one selected from the following: graphite; graphene; carbon black such as Danka black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black, etc.; carbon nanotubes (CNT) such as single-walled carbon nanotubes (SWCNT), multi-walled carbon nanotubes (MWCNT), etc.; carbon fibers such as graphite nanofibers (GNF), carbon nanofibers (CNF), activated carbon fibers (ACF), etc.; graphite such as natural graphite, artificial graphite, expanded graphite, etc.; and activated carbon, but not limited thereto. Preferably, the porous carbon material may be a carbon nanotube.
[0112] In an exemplary embodiment of the present invention, the porous carbon material may include, for example, carbon nanotubes (CNTs).
[0113] In an exemplary embodiment of the present invention, the sulfur / carbon (S / C) weight ratio of the sulfur-carbon composite material can be, for example, less than 5 g / g, more specifically less than 2.5 g / g. For example, the sulfur / carbon weight ratio of the sulfur-carbon composite material can be 2.4 g / g. When the S / C ratio of the sulfur-carbon composite material is within the above range, it can have a favorable effect on the electron transfer ability (conductivity) and electrochemical specific surface area of the sulfur-carbon composite material. For example, the available surface area of the sulfur-carbon composite material increases, and it is beneficial to suppress the leakage of sulfur from the positive electrode, but the present invention is not limited to this.
[0114] The sulfur-carbon composite material can be manufactured by any method commonly used in the art without limitation. For example, the composite material can be manufactured by simply mixing sulfur with a porous carbon material and then heat treating the mixture.
[0115] In addition to the above composition, the positive electrode active material may further include at least one selected from the group consisting of transition metal elements, Group IIIA elements, Group IVA elements, compounds of these elements with sulfur, and alloys of these elements with sulfur.
[0116] Transition metal elements may include Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Y, Zr, Nb, Mo, Tc, Ru, Rh, Pd, Os, Ir, Pt, Au, Hg, etc., Group IIIA elements may include Al, Ga, In, Tl, etc., and Group IVA elements may include Ge, Sn, Pb, etc.
[0117] In an exemplary embodiment of the present invention, the content of the sulfur-carbon composite material may be 50% by weight or more based on the total weight of the positive electrode. Specifically, based on the total weight of the positive electrode active material layer, the content of the sulfur-carbon composite material may be, for example, 80% by weight or more, 90% by weight or more, or 95% by weight or more. Specifically, based on the total weight of the positive electrode active material layer, the content of the sulfur-carbon composite material may be specifically 80 to 100% by weight, more specifically 85 to 99% by weight, 90 to 99% by weight, 95 to 98% by weight, 95 to 97% by weight, or 96% by weight. When the amount of the sulfur-carbon composite material is lower than the above range, the relative amount of auxiliary materials such as conductive materials and adhesives is high, and the amount of the sulfur-carbon composite material is low, which makes it difficult to achieve a battery with high capacity and high energy density. On the contrary, when the amount of the sulfur-carbon composite material exceeds the above range, the relative amount of conductive materials or adhesives as described below is low and the physical properties of the electrode are reduced.
[0118] The conductive material serves as a movement path for electrons from the current collector to the positive active material by electrically connecting the electrolyte to the positive active material, and may include but is not limited to any material having conductive properties as a component of the electrode that is physically different from the carbon contained in the sulfur-carbon composite material.
[0119] In an exemplary embodiment of the present invention, the conductive material may include, for example, the following substances used alone or in combination: carbon black materials such as Super-P, Danka black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black, carbon black, etc.; carbon derivatives such as carbon nanotubes, fullerenes, etc.; conductive fibers such as carbon fibers, metal fibers, etc.; fluorocarbons; metal powders such as aluminum powder and nickel powder; conductive polymers such as polyaniline, polythiophene, polyacetylene, polypyrrole, etc.
[0120] In an exemplary embodiment of the present invention, the content of the conductive material may be 0 to 10% by weight, such as 1 to 10% by weight, based on the total weight of the positive electrode active material. When the amount of the conductive material is lower than the above range, the electron transfer between the positive electrode active material and the current collector is reduced, resulting in lower voltage and capacity. On the contrary, when the amount of the conductive material exceeds the above range, the relative proportion of the positive electrode active material is low, and the total energy (charge) of the battery may be reduced. Therefore, it is preferred to determine the optimal amount within the above range.
[0121] In an exemplary embodiment of the present invention, the positive electrode may include a positive electrode active material and a binder polymer, and may not include a conductive material. That is, the positive electrode may not include any other conductive material except the porous carbon material of the sulfur-carbon composite material included in the positive electrode active material. Since the conductive material is not included, a larger amount of positive electrode active material can be included as much as possible, thereby improving the energy density and / or capacity of the lithium-sulfur battery.
[0122] The binder polymer bonds the positive electrode active material to the positive electrode current collector and interconnects the positive electrode active materials to increase bonding strength, and may include any binder polymer known in the art.
[0123] For example, the adhesive polymer may include: fluororesin adhesives, including polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), etc.; rubber adhesives, including styrene-butadiene rubber (SBR), nitrile rubber, styrene-isoprene rubber, etc.; cellulose adhesives, including carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, etc.; polyol adhesives; polyolefin adhesives, including polyethylene, polypropylene, etc.; polyimide adhesives; polyester adhesives; polyacrylate adhesives such as polyacrylic acid (PAA), etc.; silane adhesives; polyurethane adhesives; or mixtures thereof. In addition, the adhesive polymer may include copolymers containing two or more repeating units derived from these adhesives.
[0124] The content of the binder polymer may be 0.5 to 30 wt % based on 100 wt % of the positive electrode active material layer. When the amount of the binder polymer is within the above range, the physical properties of the positive electrode are improved, thereby preventing the desorption of the active material and the conductive material in the positive electrode, and appropriately controlling the ratio of the active material and the conductive material in the positive electrode, thereby ensuring the battery capacity.
[0125] In the present invention, the method of manufacturing the positive electrode for the lithium secondary battery is not particularly limited, and may include any method known to those skilled in the art or a variation thereof.
[0126] For example, the positive electrode for a lithium secondary battery may be manufactured by preparing a positive electrode slurry composition having the above-mentioned composition and coating the positive electrode slurry composition on at least one surface of a positive electrode collector to form a positive electrode active material layer.
[0127] The positive electrode slurry composition includes the positive electrode active material as described above, and may further include a binder, a conductive material, and a solvent.
[0128] The solvent includes any solvent that promotes uniform dispersion of the positive electrode active material. The solvent may include an aqueous solvent, most preferably water, and in this case, the water may be distilled water or deionized water. However, the present invention is not necessarily limited thereto, and if necessary, a lower alcohol that is easily mixed with water may be used. The lower alcohol may include methanol, ethanol, propanol, isopropanol and butanol, and preferably, a mixture of a lower alcohol and water may be used.
[0129] The solvent may be included at a concentration level sufficient to allow easy coating, and the specific amount may vary depending on the coating method and apparatus.
[0130] If necessary, the positive electrode slurry composition may further include materials commonly used in the corresponding technical field to improve functions. For example, the materials may include a viscosity modifier, a flow aid, a filler, and the like.
[0131] The method of coating the positive electrode slurry composition in the present invention is not particularly limited, and may include, for example, rod coating, doctor blade, die casting, comma coating, screen printing, dip coating, reverse roll coating, direct roll coating, gravure coating, extrusion, etc. In addition, the slurry may be coated on a substrate to form a positive electrode active material layer, and the positive electrode active material layer may be adhered to the positive electrode collector by pressing or laminating.
[0132] The coating amount of the positive electrode slurry composition on the current collector is not particularly limited and may be adjusted according to the target thickness of the positive electrode active material layer.
[0133] After coating, a drying process may be performed to remove the solvent. The drying process may be performed at an appropriate temperature and time to remove the solvent, and the conditions may vary depending on the type of solvent and are not particularly limited in the present invention. For example, the drying method may include: drying with warm air, hot air or low humidity air; vacuum drying; drying by (far) infrared radiation or electron beam radiation, etc. The drying speed is usually adjusted to remove the solvent as quickly as possible within a speed range that does not cause cracking in the positive active material layer or peeling of the positive active material layer from the positive current collector due to stress concentration.
[0134] In addition, after drying, the current collector may be pressed to increase the density of the positive electrode active material in the positive electrode. The pressing method may include molding, rolling, and the like.
[0135] The positive electrode (specifically, the positive electrode active material layer) manufactured by the above composition and manufacturing method may have a porosity of 50 to 80 volume %, specifically 60 to 75 volume %.
[0136] When the porosity of the positive electrode satisfies the range between 50 and 80 volume %, the filling level of the positive electrode active material layer comprising the positive electrode active material, the conductive material and the binder can be appropriately maintained, sufficient electrolyte can be maintained to exhibit ionic conduction and / or electrical conduction in the positive electrode active material, the output characteristics or cycle characteristics of the battery can be improved, the overvoltage and reduction in discharge capacity of the battery can be prevented, more physical and electrical connections with the collector can be achieved, the adhesion strength can be improved, and the energy density of the battery can be improved.
[0137] In an exemplary embodiment of the present invention, the positive electrode may have a capacity of 2 to 5 mAh / cm 2 For example, the sulfur (S) loading of the positive electrode can be 2 to 4 mAh / cm 2 , 2.5 to 4 mAh / cm 2 , 2.5 to 3.5 mAh / cm 2 or 2.5 to 3.0 mAh / cm 2 , but the present invention is not limited to this.
[0138] negative electrode
[0139] In an exemplary embodiment of the present invention, the negative electrode may be a current collector-less type consisting of only a negative electrode active material layer without including a current collector, or may include a negative electrode current collector and a negative electrode active material layer on at least one surface of the negative electrode current collector.
[0140] In an exemplary embodiment of the present invention, the negative electrode may include a negative electrode current collector and a negative electrode active material layer on one or both surfaces of the negative electrode current collector. Alternatively, the negative electrode may be a lithium metal plate.
[0141] The negative electrode current collector is configured to support the negative electrode active material layer as described in the positive electrode current collector.
[0142] The negative electrode active material layer may contain the negative electrode active material, and may further contain a conductive material, a binder, etc. The conductive material, the binder, etc. follow the aforementioned description.
[0143] The negative electrode active material may include a material that can reversibly insert or release lithium ions (Li + ), a material capable of reacting with lithium ions to reversibly form a lithium-containing compound, lithium metal or a lithium alloy.
[0144] Able to reversibly insert or deintercalate lithium ions (Li + ) may include, for example, crystalline carbon, amorphous carbon, or a mixture thereof. + ) to reversibly form a lithium-containing compound may include, for example, tin oxide, titanium nitrate, or silicon. The lithium alloy may include, for example, an alloy of lithium (Li) and a metal selected from the group consisting of sodium (Na), potassium (K), rubidium (Rb), cesium (Cs), francium (Fr), beryllium (Be), magnesium (Mg), calcium (Ca), strontium (Sr), barium (Ba), radium (Ra), aluminum (Al), and tin (Sn).
[0145] In an exemplary embodiment of the present invention, the negative electrode active material may be lithium metal, and specifically may be in the form of lithium metal foil or lithium metal powder.
[0146] Preferably, the negative electrode active material may be lithium metal, specifically, may be in the form of lithium metal foil or lithium metal powder.
[0147] In an exemplary embodiment of the present invention, the thickness of the negative electrode may be 40 to 80 μm. For example, the thickness of the negative electrode may be 50 to 70 μm or may be 60 μm. The thickness of the negative electrode may be measured by any known device for measuring the thickness of the components of the battery. For example, the thickness of the negative electrode may be measured using a Mitutoyo thickness gauge, but is not limited thereto.
[0148] Diaphragm
[0149] The separator separates or insulates the positive electrode from the negative electrode and enables lithium ions to be transferred between the positive electrode and the negative electrode, and is not limited to a specific type and may include any type of separator commonly used in lithium-sulfur batteries. For example, the separator may be made of a porous non-conductive or insulating material, in particular, the separator may be an independent member such as a membrane, and may also be a coating added to the positive electrode and / or the negative electrode.
[0150] In an exemplary embodiment of the present invention, the separator may preferably have low resistance to the movement of electrolyte ions and high ability to absorb electrolytes.
[0151] In an exemplary embodiment of the present invention, the separator may include a porous substrate, and the porous substrate may include any porous substrate generally used in a secondary battery, and the porous polymer film may be used alone or in a stack. For example, a non-woven fabric or a polyolefin porous film made of high melting point glass fiber, polyethylene terephthalate fiber, etc. may be used, but is not limited thereto.
[0152] In the present invention, the porous substrate is not limited to a specific material, and may include any porous substrate commonly used in electrochemical devices. For example, the porous substrate may include at least one type of material selected from the following: polyolefins such as polyethylene, polypropylene, etc.; polyesters such as polyethylene terephthalate, polybutylene terephthalate, etc.; polyamide, polyacetal, polycarbonate, polyimide, polyetheretherketone, polyethersulfone, polyphenylene oxide, polyphenylene sulfide, polyethylene naphthoate, polytetrafluoroethylene, polyvinylidene fluoride, polyvinyl chloride, polyacrylonitrile, cellulose, nylon, poly(p-phenylene benzobis[epoxy]ene), ... azoles) and polyacrylates.
[0153] In an exemplary embodiment of the present invention, the thickness of the porous substrate may be 1 to 100 μm, specifically 5 to 50 μm, but is not limited thereto. Although the thickness of the porous substrate is not limited to the above range, when the thickness is too small and below the above lower limit, when the battery is used, the mechanical properties may be reduced and the separator may be easily damaged.
[0154] In an exemplary embodiment of the present invention, the porous substrate may have an average pore diameter of 0.001 to 50 μm and a porosity of 10 to 95 volume %, but is not limited thereto.
[0155] In an exemplary embodiment of the present invention, the separator may further include a porous coating layer on at least one surface of the porous substrate, and the porous coating layer includes inorganic particles and a binder.
[0156] In an exemplary embodiment of the present invention, the inorganic particles and the binder included in the porous coating layer are not particularly limited and may include inorganic particles and binders commonly used in the porous coating layer of the separator, and the manufacturing method thereof is not particularly limited.
[0157] Electrolyte
[0158] The electrolyte is a medium for movement of ions participating in the electrochemical reaction of the lithium-sulfur battery, and contains a non-aqueous solvent and a lithium salt as an electrolyte.
[0159] The electrolyte is not limited to a specific type, and may include any electrolyte having a composition that can be used in a lithium secondary battery, particularly a lithium-sulfur battery.
[0160] In an exemplary embodiment of the present invention, the electrolyte may include a non-aqueous solvent, a lithium salt, and an additive.
[0161] In an exemplary embodiment of the present invention, the non-aqueous solvent is not limited to a specific type and may include any type of non-aqueous solvent that can be used in a lithium-sulfur battery. For example, the non-aqueous solvent may include ether solvents, esters, amides, linear carbonates, cyclic carbonates, and the like.
[0162] In an exemplary embodiment of the present invention, the ester may include, for example, any one selected from the group consisting of methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, γ-butyrolactone, γ-valerolactone, γ-caprolactone, σ-valerolactone and ε-caprolactone or a mixture thereof, but is not limited thereto.
[0163] In an exemplary embodiment of the present invention, the linear carbonate may include, for example, any one selected from the group consisting of dimethyl carbonate, diethyl carbonate, dipropyl carbonate, ethyl methyl carbonate, methyl propyl carbonate, and ethyl propyl carbonate, or a mixture thereof, but is not limited thereto.
[0164] In an exemplary embodiment of the present invention, the cyclic carbonate may include, for example, any one selected from the following or a mixture thereof: ethylene carbonate, propylene carbonate, 1,2-butylene carbonate, 2,3-butylene carbonate, 1,2-pentylene carbonate, 2,3-pentylene carbonate, vinylene carbonate, vinyl ethylene carbonate and halides thereof. Halides include, for example, fluoroethylene carbonate, etc., but are not limited thereto.
[0165] In an exemplary embodiment of the present invention, the non-aqueous solvent may include an ether solvent.
[0166] In an exemplary embodiment of the present invention, the content of the ether solvent may be 60% by volume or more, for example, 60 to 100% by volume, 70 to 100% by volume, 80 to 100% by volume, 85 to 100% by volume, 90 to 100% by volume, 95 to 100% by volume, 98 to 100% by volume, 90 to 98% by volume, or 90 to 95% by volume, based on the total volume of the non-aqueous solvent. When the amount of the ether solvent is within the above range, it may have a favorable effect on the solubility of components of the electrolyte such as lithium salts, etc., but the present invention is not limited thereto.
[0167] In an exemplary embodiment of the present invention, the ether solvent may include an acyclic ether, a cyclic ether, or a mixture thereof.
[0168] In an exemplary embodiment of the present invention, the acyclic ether may include, for example, at least one selected from the group consisting of dimethyl ether, diethyl ether, dipropyl ether, dibutyl ether, diisobutyl ether, ethyl methyl ether, ethyl propyl ether, ethyl tert-butyl ether, dimethoxymethane, trimethoxymethane, dimethoxyethane, diethoxyethane, dimethoxypropane, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, triethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, ethylene glycol divinyl ether, diethylene glycol divinyl ether, triethylene glycol divinyl ether, dipropylene glycol dimethylene ether, butylene glycol ether, diethylene glycol ethyl methyl ether, diethylene glycol isopropyl methyl ether, diethylene glycol butyl methyl ether, diethylene glycol tert-butyl ethyl ether, and ethylene glycol ethyl methyl ether. Preferably, the acyclic ether may include at least one selected from the group consisting of dimethyl ether, dimethoxyethane, diethoxyethane, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, and tetraethylene glycol dimethyl ether, more preferably dimethoxyethane.
[0169] In an exemplary embodiment of the present invention, the cyclic ether may include, for example, at least one selected from the group consisting of 2-methylfuran, 1,3-dioxolane, 4,5-dimethyldioxolane, 4,5-diethyldioxolane, 4-methyl-1,3-dioxolane, 4-ethyl-1,3-dioxolane, tetrahydrofuran, 2-methyltetrahydrofuran, 2,5-dimethyltetrahydrofuran, 2,5-dimethoxytetrahydrofuran, 2-ethoxytetrahydrofuran, 2-methyl-1,3-dioxolane, 2-vinyl-1,3-dioxolane, 2,2-dimethyl-1,3-dioxolane, 2-methoxy-1,3-dioxolane, 2-ethyl-2-methyl-1,3-dioxolane, tetrahydropyran, 1,4-dihydropyran, 1,4-dihydropyran, 2,5-dimethyltetrahydrofuran, 2,5-dimethoxytetrahydrofuran, 2-ethoxytetrahydrofuran, 2-methyl-1,3-dioxolane, 2-vinyl-1,3-dioxolane, 2,2-dimethyl-1,3-dioxolane, 2-methoxy-1,3-dioxolane, 2-ethyl-2-methyl-1,3-dioxolane, tetra ... Preferably, the cyclic ether may include at least one selected from the group consisting of 2-methylfuran, 1,3-dioxolane, tetrahydrofuran, 2-methyltetrahydrofuran and 2,5-dimethyltetrahydrofuran, more preferably 2-methylfuran.
[0170] In an exemplary embodiment of the present invention, the nonaqueous solvent may include a mixture of an acyclic ether and a cyclic ether.
[0171] In an exemplary embodiment of the present invention, the non-aqueous solvent may include dimethoxyethane (DME) and 2-methylfuran (2-MeF).
[0172] In an exemplary embodiment of the present invention, the volume ratio of the acyclic ether to the cyclic ether may be 5:95 to 95:5 (volume / volume), specifically 95:5 to 50:50, more specifically 90:10 to 50:50, 90:10 to 70:30, 85:15 to 75:25 or 80:20 (volume / volume). In the present invention, the volume ratio corresponds to the ratio of "volume % of acyclic ether": "volume % of cyclic ether" in the ether solvent.
[0173] In an exemplary embodiment of the present invention, in terms of the solubility of the electrolyte, the non-aqueous solvent may not include a carbonate solvent. Alternatively, the non-aqueous solvent may include a carbonate solvent in a small amount such that the carbonate solvent does not affect the solubility of the lithium salt. For example, when the non-aqueous solvent includes a carbonate solvent, based on the gross weight of the lithium secondary battery electrolyte, the content of the carbonate solvent may be 3% by weight or less, 2% by weight or less, 1% by weight or less, 0.5% by weight or less, or 0% by weight (i.e., zero).
[0174] In an exemplary embodiment of the present invention, the lithium salt may include any lithium salt commonly used as an electrolyte for a lithium-sulfur battery without limitation. The lithium salt may include, for example, LiCl, LiBr, LiI, LiClO4, LiBF4, LiB 10 Cl 10 , LiPF6, LiCF3SO3, LiCF3CO2, LiC4BO8, LiAsF6, LiSbF6, LiAlCl4, CH3SO3Li, CF3SO3Li, (CF3SO2)2NLi, (C2F5SO2)2NLi, (SO2F)2NLi, (CF3SO2)3CLi, lithium chloroborate, lower aliphatic lithium carbonate, lithium tetraphenylborate, lithium imide or two or more thereof.
[0175] In an exemplary embodiment of the present invention, the concentration of the lithium salt may be appropriately determined according to ion conductivity, solubility, etc. For example, the concentration of the lithium salt may be 0.1 to 4 M, preferably 0.2 to 2 M, 0.2 to 1 M, 0.5 to 2 M, 0.6 to 1 M, or 0.6 to 0.9 M. When the concentration of the lithium salt is within the above range, ion conductivity suitable for battery operation or appropriate viscosity of the electrolyte may be advantageously ensured, thereby improving the mobility of lithium ions and suppressing the decomposition reaction of the lithium salt itself, but the present invention is not limited thereto.
[0176] In an exemplary embodiment of the present invention, the additive may further include a nitrogen compound in addition to the lithium salt to improve the conductivity of the electrolyte and the life of the lithium-sulfur battery.
[0177] Specifically, the effect of the nitrogen compound is not limited thereto, but for example, the nitrogen compound can inhibit the reduction reaction of polysulfides during the charge and discharge process of the lithium-sulfur battery, thereby preventing the irreversible consumption of polysulfides and improving the performance of the lithium-sulfur battery.
[0178] In an exemplary embodiment of the present invention, the nitrogen compound is not limited to a specific type, and may include any nitrogen compound that stably forms a solid electrolyte interface (SEI) layer of the negative electrode and improves charge and discharge efficiency. For example, the nitrogen compound may include a nitrate compound, a nitrite compound, or a mixture thereof.
[0179] In an exemplary embodiment of the present invention, the nitrogen compound can be selected, for example, from: inorganic nitrate or nitrite compounds such as lithium nitrate (LiNO3), potassium nitrate (KNO3), cesium nitrate (CsNO3), barium nitrate (Ba(NO3)2), ammonium nitrate (NH4NO3), lithium nitrite (LiNO2), potassium nitrite (KNO2), cesium nitrite (CsNO2), ammonium nitrite (NH4NO2), etc.; organic nitrate or nitrite compounds such as methyl nitrate, dialkyl imidazole nitrate , guanidine nitrate, imidazole nitrate , pyridine nitrate , ethyl nitrite, propyl nitrite, butyl nitrite, amyl nitrite, octyl nitrite, etc.; organic nitro compounds such as nitromethane, nitropropane, nitrobutane, nitrobenzene, dinitrobenzene, nitropyridine, dinitropyridine, nitrotoluene, dinitrotoluene, etc.; and combinations thereof, and preferably lithium nitrate.
[0180] In an exemplary embodiment of the present invention, the content of the nitrogen compound may be, for example, 1 to 10 wt %, specifically 1 to 7 wt %, 1 to 5 wt %, based on the total weight of the electrolyte, but is not limited thereto. When the nitrogen compound is included in the above amount, the nitrogen compound may have a more favorable effect on improving the conductivity of the electrolyte and the reduction inhibition of polysulfides when used in a lithium-sulfur battery, but the present invention is not limited thereto.
[0181] In an exemplary embodiment of the present invention, the weight ratio of the electrolyte of the lithium-sulfur battery to the sulfur (S) in the sulfur-carbon composite material (E1 / S weight ratio) may be 2.7 g / g or more, 2.8 g / g or more, 2.9 g / g or more, or 3.0 g / g or more. For example, the E1 / S ratio may be 2.7 to 4.0 g / g, 2.8 to 3.7 g / g, 2.9 to 3.5 g / g, 3.0 to 3.5 g / g, 2.8 to 3.4 g / g, 2.9 to 3.4 g / g, or 3.0 to 3.4 g / g. Here, E1 represents the weight of the electrolyte, and S represents the weight of sulfur (S) contained in the positive electrode.
[0182] When the ratio of the weight of the electrolyte to the weight of sulfur in the positive electrode of the lithium-sulfur battery (E1 / S) satisfies the above range, the reduction reaction of the positive electrode active material during discharge of the lithium-sulfur battery at a high C rate can be enhanced. In addition, when discharged at a high C rate, the capacity may be significantly improved, and the capacity decrease may be less than the capacity decrease at a low C rate.
[0183] In an exemplary embodiment of the present invention, the El / S ratio of the lithium-sulfur battery can be calculated by the ratio of the weight of the electrolyte to the weight of the sulfur in the sulfur-carbon composite material of the positive electrode in the manufacturing step just after the lithium-sulfur battery is manufactured.
[0184] In another exemplary embodiment of the present invention, the El / S ratio of the lithium-sulfur battery can be calculated by the ratio of the weight of the electrolyte to the weight of the sulfur in the sulfur-carbon composite material of the positive electrode analyzed by disassembling the battery.
[0185] For example, when analyzing the El / S ratio of a lithium-sulfur battery by disassembling the battery, the total weight of the lithium-sulfur battery in a charged state can be measured and disassembled into a positive electrode, a negative electrode, a separator and a shell, followed by washing with a solvent and drying, and then the sum of the weights of the components can be obtained, and the weight of the electrolyte can be measured by subtracting the weight of the positive electrode, the negative electrode, the separator and the shell from the total weight of the battery. In this case, the solvent used for washing preferably includes any solvent that extracts the electrolyte from the positive electrode, the negative electrode, the separator and the shell. Subsequently, the positive electrode active material layer and the current collector can be separated from the dried positive electrode, and the weight of the sulfur derived from the sulfur-carbon composite material present in the positive electrode active material layer can be measured to measure the weight of sulfur in the positive electrode. In this way, the El / S ratio of the lithium-sulfur battery can be calculated by the ratio of the weight of the electrolyte to the weight of sulfur in the sulfur-carbon composite material of the positive electrode.
[0186] In an exemplary embodiment of the present invention, a method for measuring the weight of sulfur derived from a sulfur-carbon composite material present in a positive electrode active material layer may include, for example, performing thermogravimetric analysis (TGA) on a resulting product obtained by stripping the resulting positive electrode active material layer to measure the amount of sulfur (S) derived from the active material, but the measuring method is not limited thereto.
[0187] In an exemplary embodiment of the present invention, the lithium-sulfur battery may be disassembled at a fully charged state, ie, SOC 100%.
[0188] In another exemplary embodiment of the present invention, the lithium-sulfur battery may be disassembled at SOC 95% to SOS 100%.
[0189] In an exemplary embodiment of the present invention, when disassembling a lithium-sulfur battery in a charged state, the disassembly may be performed under an inert atmosphere for safety purposes. For example, the disassembly of the lithium-sulfur battery may be performed under an Ar atmosphere.
[0190] In an exemplary embodiment of the present invention, the lithium-sulfur battery may have an energy density of 300 Wh / kg or more. For example, the energy density of the lithium-sulfur battery may be 300 to 500 Wh / kg or 300 to 400 Wh / kg.
[0191] In an exemplary embodiment of the present invention, the energy density of a lithium-sulfur battery at a high discharge rate can be maintained at the energy density level at a low discharge rate.
[0192] For example, the energy density of a lithium-sulfur battery measured at a 1.0C discharge rate may be more than 90% of the energy density measured at a 0.5C discharge rate.
[0193] In addition, the energy density of the lithium-sulfur battery measured at a 2.0C discharge rate can be more than 90% of the energy density measured at a 1.0C discharge rate.
[0194] In an exemplary embodiment of the present invention, the energy density of the lithium-sulfur battery can be measured by any known method, and the measuring method is not particularly limited. For example, the energy density of the lithium-sulfur battery can be calculated according to the following mathematical formula by performing a step of discharging from 2.5 V to 1.8 V at a rate of 0.5 C at room temperature and a step of charging to 2.5 V at a rate of 1.0 C, and then discharging at a constant rate selected from a range of 0.5 to 2.0 C.
[0195] [Mathematical formula]
[0196] Energy density (Wh / kg) = {[(discharge capacity (mAh) × driving voltage (V)) / 1000] / (battery weight (kg))}
[0197] In an exemplary embodiment of the present invention, the room temperature may be, for example, 23°C to 25°C, specifically 23°C.
[0198] In an exemplary embodiment of the present invention, the specific capacity of the lithium-sulfur battery may be, for example, 1,000 mAh / g or more.
[0199] In an exemplary embodiment of the present invention, the specific capacity of the lithium-sulfur battery can be measured, for example, by performing a discharge step at a 0.5C rate in the range between 1.8 V and 2.5 V at room temperature, followed by charging and discharging at a 0.5C rate.
[0200] In an exemplary embodiment of the present invention, the room temperature may be 23°C to 25°C.
[0201] In an exemplary embodiment of the present invention, the lithium-sulfur battery may be a coin-type battery, a pouch-type battery, or a cylindrical battery, but is not limited thereto.
[0202] According to another aspect of the present invention, a method for evaluating high-output characteristics of a lithium-sulfur battery using the above-mentioned Mathematical Formula 1 is provided.
[0203] The evaluation method includes the step of determining a lithium-sulfur battery having a ratio R (1.0C / 0.5C) of 80% or more as a high-power battery, the ratio satisfying the above-mentioned Mathematical Formula 1.
[0204] In an exemplary embodiment of the present invention, the high output battery may be, for example, a battery that maintains an energy density of 300 Wh / kg or more under a discharge condition of 1.0 C rate or more at room temperature. In this case, in an exemplary embodiment of the present invention, the room temperature may be 23° C. to 25° C.
[0205] Hereinafter, the present invention will be described in more detail by way of examples. However, the following examples are for illustrative purposes only, and the scope of the present invention is not limited thereto.
[0206] [Manufacturing of lithium-sulfur batteries]
[0207] Example 1
[0208] As a positive electrode active material, a sulfur-carbon composite material (S / C weight ratio = 2.3 g / g) in which sulfur (S8) was loaded onto carbon nanotubes (MWCNT) was prepared. The prepared sulfur-carbon composite material and polyacrylic acid (PAA) as a binder were added to water at a weight ratio of 96:4 to prepare a positive electrode slurry composition. The positive electrode slurry composition was coated on an aluminum current collector and dried to manufacture a positive electrode. The loading capacity of the positive electrode was 2.7 mAh / cm 2 .
[0209] A lithium metal with a thickness of 60 μm was prepared as a negative electrode.
[0210] The positive electrode and the negative electrode were placed with a polyethylene separator having a thickness of 16 μm and a porosity of 46 volume % therebetween to prepare an electrode assembly.
[0211] The prepared electrode assembly was placed in a pouch-type case, and an electrolyte containing 0.75 M lithium salt (LiTFSI) and 3 wt % lithium nitrate (LiNO3) dissolved in an 8:2 (volume / volume) mixed solvent of dimethoxyethane and 2-methylfuran (2-MeF) was injected into the pouch-type case at an El / S ratio of 3.0 g / g to manufacture a lithium-sulfur battery.
[0212] Example 2
[0213] A lithium-sulfur battery was manufactured in the same manner as in Example 1, except that the electrolyte was injected at an El / S ratio of 3.4 g / g.
[0214] Comparative Example 1
[0215] A lithium-sulfur battery was manufactured in the same manner as in Example 1, except that the electrolyte was injected at an El / S ratio of 2.6 g / g.
[0216] [Analysis of the amount of Li2S produced and evaluation of battery performance]
[0217] The lithium-sulfur batteries of Example 1, Example 2, and Comparative Example 1 were charged to 2.4 V at a 0.5 C rate at room temperature (23° C.), and discharged to 1.8 V at a 0.5 C rate, a 1.0 C rate, or a 2.0 C rate. In this case, the battery capacity (mAh / g) and the energy density (Wh / kg) were measured and divided by the battery capacity. Figure 1 and Figure 2The results of evaluating specific capacity (mAh) and energy density (Wh) are shown.
[0218] Figure 3 is a graph showing the average discharge voltage, ie, the nominal voltage of the battery at each discharge at a 0.5C rate and a 1.0C rate.
[0219] refer to Figure 1 It was confirmed that the energy density of the lithium-sulfur batteries of Examples 1 and 2 decreased slightly when discharged at a rate of 2.0C (both remained above 300 Wh / kg), while the energy density of the lithium-sulfur battery of Comparative Example 1 decreased significantly.
[0220] Figure 2 This is a graph of a lithium-sulfur battery discharged at a rate of 2.0 C to 1.8 V. It was confirmed that the lithium-sulfur batteries of Examples 1 and 2 showed a specific capacity of 1,000 mAh / g or more, whereas the lithium-sulfur battery of Comparative Example 1 showed a very low specific capacity.
[0221] It was confirmed that the E / S of the lithium-sulfur battery of Comparative Example 1 was 2.6, indicating that the capacity and energy density were significantly reduced at a discharge rate of 2.0 C.
[0222] refer to Figure 1 and Figure 3 It was confirmed that Comparative Example 1 maintained an energy density of more than 300 Wh / kg, but showed a much lower nominal voltage than Example 1 or Example 2 when discharged at 1.0C.
[0223] Figure 4 and Figure 5 The results of analyzing the amount of Li2S in the lithium-sulfur batteries of Example 1, Example 2, and Comparative Example 1 after discharging to 1.8 V (DoD 100) at 0.5C or 1.0C are shown.
[0224] In order to measure the amount of Li2S in the lithium-sulfur battery at each discharge state, the XRD patterns of the lithium-sulfur battery at the discharge state were obtained by the following method.
[0225] First, an XRD pattern was obtained when each battery was discharged in the range of 2.4 to 1.8 V at a 0.5C rate or a 1.0C rate at room temperature (23°C). Specifically, the XRD pattern was obtained by measuring 2theta (2θ) in the range of 4° to 17° in transmission mode using Mo Kα X-rays (λ=0.709Å) of PANalyical Empyrean XRD, and one pattern can be obtained at intervals of 0.014° and for a total of 1 minute. In this case, the XRD measurement was performed using a pressing fixture equipped with a Be window. Figure 4 and Figure 5In the scattering peak intensity is measured in arbitrary units (au).
[0226] In the X-ray diffraction spectrum, Li2S has a range of 1.85 to 1.92 Å. -1 The scattering vector (q) region has a characteristic peak. The amount of Li2S can be determined from the peak intensity (i.e., scattering intensity).
[0227] The characteristic peak of Li2S can be found by the scattering vector (q) at 1.4 to 1.6 / Å. However, the scattering vector of Li2S and the scattering vector of S8 may overlap in the corresponding region, so in this experiment, in order to quantify Li2S, a specific peak at 1.85 to 1.92 / Å was used.
[0228] Figure 4 and Figure 5 They show the discharge rate at 0.5C ( Figure 4 ) and 1.0C discharge rate ( Figure 5 ) is a graph of the Li2S peak intensity measured under . Figure 4 and Figure 5 The results were used to calculate the ratio R (1.0C / 0.5C) of lithium sulfide according to the following Mathematical Formula 1 and are shown in the following Table 1.
[0229] [Mathematical formula 1]
[0230] R(1.0C / 0.5C)=[A(DoD 100) 1.0C / A(DoD 100) 0.5C ]×100 (%)
[0231] In the above mathematical formula 1, A(DoD 100) 1.0C is the amount of lithium sulfide (Li2S) present in the state discharged to DoD 100 at 1.0C, and
[0232] A(DoD 100) 0.5C It is the amount of lithium sulfide (Li2S) present in the state of being discharged to DoD 100 at 0.5C.
[0233] In this case, A(DoD 100) is measured by the peak intensity value of the XRD pattern. 1.0C and A(DoD 100) 0.5C .
[0234]
[0235] refer to Figure 4 and Figure 5 As shown in Table 1, the amount of Li2S generated when the lithium-sulfur battery of Comparative Example 1 was discharged at 1.0C was confirmed to be very small.
[0236] From these results, it was confirmed that Examples 1 and 2 having a lithium sulfide ratio R (1.0C / 0.5C) of 85% or more had high output characteristics, whereas Comparative Example 1 having a low ratio did not have high output characteristics.
[0237] Although the present invention has been described above with reference to a limited number of examples and drawings, the present invention is not limited thereto and it will be apparent to those skilled in the art that various modifications and variations may be made to the present invention within the technical aspects of the present invention and the scope of the appended claims and their equivalents.
Claims
1. A lithium-sulfur battery, comprising: a positive electrode; a negative electrode; a separator between the positive electrode and the negative electrode; and an electrolyte, wherein the positive electrode has a positive electrode active material comprising a sulfur-carbon composite material, and The lithium-sulfur battery has a ratio R (1.0C / 0.5C) of more than 80%, and the ratio satisfies the following mathematical formula 1: [Mathematical formula 1] R(1.0C / 0.5C)=[A(DoD 100) 1.0C / A(DoD 100) 0.5C ]×100 (%) In mathematical formula 1, A(DoD 100) 1.0C is the amount of lithium sulfide (Li2S) present at a depth of discharge (DoD) of 100 after discharge at 1.0C, and A(DoD 100) 0.5C is the amount of lithium sulfide (Li2S) present at DoD 100 after discharge at 0.5C.
2. The lithium-sulfur battery according to claim 1, wherein the R(1.0C / 0.5C) is greater than 85%. 3 . The lithium-sulfur battery according to claim 1 , wherein the DoD 100 is in a state having a potential of 1.7 V to 1.9 V. 4 . The lithium-sulfur battery according to claim 1 , wherein the DoD 100 is in a state having a potential of 1.8 V.
5. The lithium-sulfur battery according to claim 1, wherein the amount of the lithium sulfide (Li2S) is the weight, volume or molar number of the lithium sulfide.
6. The lithium-sulfur battery according to claim 1, wherein the ratio R (1.0C / 0.5C) is measured by the ratio of the peak intensity of the lithium sulfide (Li2S) in the X-ray diffraction spectrum of the lithium-sulfur battery, and The lithium sulfide (Li2S) has a peak at 1.85 Å in the X-ray diffraction spectrum. -1 to 1.92 Å -1 There is a characteristic peak in the scattering vector (q) region.
7. The lithium-sulfur battery according to claim 1, wherein the weight ratio of the electrolyte to the sulfur (S) in the sulfur-carbon composite material (E1 / S weight ratio) is 2.7 g / g or more.
8. The lithium-sulfur battery according to claim 1, wherein the electrolyte comprises a non-aqueous solvent, a lithium salt and an additive. 9 . The lithium-sulfur battery according to claim 1 , wherein the energy density of the lithium-sulfur battery is greater than 300 Wh / kg. 10 . The lithium-sulfur battery according to claim 1 , wherein the amount of sulfur (S) in the sulfur-carbon composite material is 60 wt % to 85 wt %. 11 . The lithium-sulfur battery according to claim 1 , wherein the weight of the sulfur-carbon composite material is 90 wt % or more based on the total weight of the positive electrode. 12 . The lithium-sulfur battery according to claim 1 , wherein the lithium-sulfur battery is a coin-type battery, a pouch-type battery or a cylindrical battery.
13. A method for evaluating output characteristics of a lithium-sulfur battery, the lithium-sulfur battery comprising: a positive electrode; a negative electrode; a separator between the positive electrode and the negative electrode; and an electrolyte, wherein the positive electrode has a positive electrode active material comprising a sulfur-carbon composite material, The evaluation method comprises the following steps: When the ratio R (1.0C / 0.5C) according to the following mathematical formula 1 is 80% or more, it is determined to be a high-power lithium-sulfur battery, [Mathematical formula 1] R(1.0C / 0.5C)=[A(DoD 100) 1.0C / A(DoD 100) 0.5C ]×100 (%) In mathematical formula 1, A(DoD 100) 1.0C is the amount of lithium sulfide (Li2S) present at DoD 100 after discharge at 1.0C, and A(DoD 100) 0.5C is the amount of lithium sulfide (Li2S) present at DoD 100 after discharge at 0.5C. 14 . The evaluation method according to claim 13 , wherein the high-power lithium-sulfur battery is a battery that maintains an energy density of 300 Wh / kg or more under a discharge condition of 1.0 C rate or more at room temperature. The evaluation method according to claim 14 , wherein the room temperature is 23° C. to 25° C.
16. The evaluation method according to claim 15, wherein A(DoD 100) xC (x = 0.5 or 1.0) by the X-ray diffraction spectrum obtained at DoD 100 after the lithium-sulfur battery was discharged at x C rate at 1.85 Å -1 to 1.92 Å -1 The peak intensity value in the scattering vector (q) region is measured, and Herein the ratio R (1.0C / 0.5C) is measured by calculating the ratio of the obtained peak intensities.
Citation Information
Patent Citations
Affinity chromatography device comprising a heat-treated fibrillated polymer membrane and a manifold comprising the same
KR1020230066600A